Governance and Upgrading in GVC: Why Embeddedness Matters? - Forte, Paulo Jordão Oliveira Cerqueira (2019)
Purpose – [This study’s primary objective is to propose actors embeddeness as a source for governance and upgrading within the GVC (Global Value Chain) framework.] Design/methodology/approach – [This study uses co-word analysis to study GVC scientific production. The analysis is conducted using the controversies mapping from the Theory of Scientific and Technological Change (TSTC)] Findings – [Two theoretical gaps were pointed due to GVC theory evolvement. First, that governance and upgrading have more than one definition and second that value and network are upgrading strategies. This article proposes the use of Montenegro e Bulgacov (2014) framework to translate governance and upgrading respectively as network governance and strategic outcomes.  Embeddedness matters because is a stable theoretical concept (Granovetter, 1985) that can be a link between network governance and strategic results.] Originality/value – [The study main contribution is to propose a relativist embeddeness sourcing governance and upgrading. The second contribution is to present a framework, ANT based, modeled to study governance and its strategic results.]